Students’ Perception of Artificial Intelligence (AI) as English Learning Tools at MTsN 4 North Aceh - Bungsu Keumalasari; Muhammad Iqbal; Farada Aulia; Alam Fahlevi Pranata (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research investigates students’ perceptions of Artificial Intelligence (AI) as a tool for learning English at MTsN 4 North Aceh. Quantitative descriptive method was employed in this study that involving 40 students as participants. Data were collected through Likert-scale questionnaires and semi-structured interviews to assess students’ attitudes towards AI in relation to motivation, and skill development (listening, speaking, reading, and writing). The results indicate that most students perceive AI positively, appreciating its ability to enhance their understanding of English materials, increase motivation, and provide real-time feedback. Many students highlighted that AI tools offered interactive and flexible learning opportunities. Overall, artificial intelligence (AI) is not seen as a replacement for conventional teaching, even though it is a useful tool for learning English. The best strategy could be to combine AI with human instruction, maintaining a balance between the flexibility and immediate feedback that AI offers and the individualized help that teachers can provide.